AGAMA DASAR FILSAFAT TEOLOGIS PLURALISME - Purwanto (Jurnal Sarita Bahalap, 2025)
Abstrak Philosophical basis also plays an important role in human understanding to think and provide arguments about what is in the situation where he is. However, people still philosophize and try to achieve success in sharpening their knowledge or to find out what they have been questioning in their life. But this cannot answer his criticism of the Bible or of the existence of God. Because, only God's Word is able to reach absolute understanding and truth in accepting God's existence by faith. Keywords : analitical, philosophy,theolgloy,pluralism Abstrak Dasar filosofis selalu menjadi hal yang penting dalam berpikir dan bahkan dalam berargumentasi. Meskipun banyak filsuf telah berhasil dalam ilmu pengetahuan, namun tidak dapat memberi jawab atas semua hal mengenai kehidupan. Tentu para filsuf tidak sanggup memahami keberadaan Tuhan, karena hanya Firman Tuhan yang dapat menjangkau kemutlakan pemahaman dan kebenaran itu hanya dapat diterima dengan iman. Kata kunci : analisis, filsafat,theology, pluralisme